The Emergence of Rice and Millet Farming in the Zang-Yi Corridor of Southwest China Dates Back to 5000 Years Ago - Huan, Xiujia; Deng, Zhenhua; Zhou, Zhiqing; Yan, Xue; Hao, Xiaoxiao; Bu, Qi; Lu, Houyuan (Frontiers in Earth Science, 2022)
The Zang-Yi Corridor is of pivotal significance for the interactions between northwest China, southwest China, and mainland Southeast Asia. It has been hypothesized that the formation of mixed farming in this region and its surrounding areas was based on multiple waves of crop dispersal, with foxtail millet and broomcorn millet arriving first from northwest China around 5300 cal. BP and rice from middle Yangtze valley after 4700 cal. BP. Based on the systematic sampling and direct dating conducted at the Guijiabao site, Sichuan Province, this study demonstrates that by no later than 5000 cal. BP, mixed farming had already emerged in the south part of Zang-Yi corridor, which was much earlier than expected before. With this new evidence, it is argued that the transformation into farming in Southwest China was based on the dispersal of a crop package comprising foxtail millet, broomcorn millet, and rice instead of different waves of introduction. A further comparison of all archaeobotanical data in this region revealed that crop patterns varied significantly between different sites because of their diverse environmental conditions.